A Difficult Equation: The Search for Identity in the Poetry of Diego Bastianutti - Logan, Katharina (Italian Canadiana, 2024)
Diego Bastianutti’s poetry is part of a cathartic process of coming to terms with his exile from Fiume during the Julian-Dalmatian exodus immediately following the Second World War. This article analyzes Bastianutti’s poetry, focusing on his process of coming to terms with his exile and his multi-layered cultural identity. His self-identification as mestizo, a Spanish term usually used to describe someone of mixed Spanish and Indigenous descent, and then as an antevasin, a Sanskrit term for a border-dweller, emerge as solutions to, or rationalizations for, the problem of the pain Bastianutti wrestles with as a result of his exile, displacement, and emigration.